The physical and psychological impact of using a computer-based environmental control system: a case study. (21st January 2013) - Squires, Luke A.; Rush, Frank; Hopkinson, Andrew; Val, Morrison
Abstract: Purpose: To evaluate a new computer-based environmental control system, Subvenio, in terms of its physical and psychological impact in a single case study of a 46-year-old woman with a severe physical disability, tetraplegia. Expectations of the system and factors relating to successful Subvenio use were also sought. Method: A longitudinal questionnaire measured function (BI; FAI), mental health and wellbeing (GHQ-12; WHO-5) 6 weeks before, and 10 and 26 weeks after Subvenio installation. Expectations and Subvenio experience were explored through open-ended questions. Daily assessment of mood and Subvenio use was also recorded for a one-week period in-between each time point. Results: Data obtained did not suggest changes in global functioning or emotional wellbeing whilst activity increased for specific everyday tasks such as turning on the lights and television. Qualitatively, other benefits of Subvenio were identified such as independence and less reliance on carers. Conclusions: Computer-based assistive technology (AT) points to qualitative benefits for this individual, encouraging further research with larger samples. Various factors facilitated Subvenio use and the benefits derived from it, including device factors and personal characteristics (e.g. pain). Healthcare and service providers should communicate with AT/environmental control system users about these factors before and during provision to maximise benefits and limit AT abandonment. Implications for Rehabilitation: One implication from this study is that AT development should focus on the factors influencing successful AT use. In this study notably, optimism, expectations of AT, pain, symptom changes and service delivery are all highlighted. Communication between AT service providers and AT users is encouraged to prevent unrealistic expectations of AT equipment, and such communication should continue throughout AT use to ensure the equipment is still meeting the user needs. An integration of quantitative and qualitative methods of data collection is encouraged in order to fully understand the relationship between AT/ECS and physical and psychological outcomes due to the differences yielded. As seen in our data, ECS has the potential to save money and time with reports of reduced care received and reduced negative attitudes to receiving care. The response of carers to this requires further research so that their perception and experience of AT/ECS is taken into account.